2004
DOI: 10.1111/j.1471-4159.2004.02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress induces activation of stress‐activated kinases in the mouse brain

Abstract: Stress is a part of daily life. However, molecular mechanisms underlying the activation of limbic-hypothalamic-pituitaryadrenal (LHPA) axis remains unknown. In this study, we explored whether activation of the mitogen-activated kinase kinase 4 (MKK4)-c-Jun-N-terminal kinase (JNK) signaling pathway may play a role in the activation of the LHPA axis. We found that forced-swim stress induced elevation of activated MKK4 in the hippocampal formation, amygdala, and hypothalamus. Unlike MKK4, a high basal level of JN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
4
42
2
Order By: Relevance
“…This assumption is further corroborated by data showing selective activation of JNKs in the hippocampal formation, and in discrete nuclei of the hypothalamus and the amygdala, which represent brain regions that play a critical role in the induction and regulation of stress responses (McEwen, 2007). Moreover, that all the aforementioned studies demonstrate activation of JNKs in the hippocampus reinforces the likelihood that JNKs signaling is crucially involved in the formation of stressassociated emotional memories (Liu et al, 2004;Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This assumption is further corroborated by data showing selective activation of JNKs in the hippocampal formation, and in discrete nuclei of the hypothalamus and the amygdala, which represent brain regions that play a critical role in the induction and regulation of stress responses (McEwen, 2007). Moreover, that all the aforementioned studies demonstrate activation of JNKs in the hippocampus reinforces the likelihood that JNKs signaling is crucially involved in the formation of stressassociated emotional memories (Liu et al, 2004;Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 64%
“…Although authors reported that two forms of acute stress yielded somewhat different regional patterns of JNKs activation, it might have been that these differences resulted from the different rodent species and stress procedures used. More importantly, such dependence of the pJNK expression pattern on the nature, and particularly, on the relative strength of acute stress (Liu et al, 2004) may explain why exposure to immediate foot shock alone did not elevate hippocampal pJNK levels in a manner similar to prolonged immobilization stress. This assumption is further corroborated by data showing selective activation of JNKs in the hippocampal formation, and in discrete nuclei of the hypothalamus and the amygdala, which represent brain regions that play a critical role in the induction and regulation of stress responses (McEwen, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice subjected to chronic swim stress, for example, exhibit an elevation of kinase activity in brain (29). To determine whether K ir 3.1 phosphorylation occurred in response to stimuli minimally involved in nociception, we exposed mice to a modified Porsolt swim-stress protocol (see "Experimental Procedures") and performed Western immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The known signaling pathways that mediate the effects of the neurotrophic factors on Bcl-2 and Bcl-xl are the Rsk/MAP pathway, JNK pathway, and the PI-3K/AKT pathway (Manji and Duman, 2001;Bonni et al, 1999;Riccio et al, 1999). Stressors such as forced-swim and restraint stress induce activation of the MKK4-JNK signaling pathway in the hippocampus, amygdala, and hypothalamus (Liu et al, 2004). Although stimulation of this signaling pathway acutely influences the phosphorylation states and membrane translocations of the apoptotic proteins, it is possible that long-term sustained stimulation of this pathway as well as circulating glucocorticoids caused by chronic stress downregulates Bcl-2 and Bcl-xl gene expression as a compensatory response.…”
Section: Discussionmentioning
confidence: 99%